Marriage and Masculinity: Male-Breadwinner Culture, Unemployment, and Separation Risk in 29 Countries. Issue 3 (June 2021) - Gonalons-Pons, Pilar; Gangl, Markus
Scholars argue that gender culture, understood as a set of beliefs, norms, and social expectations defining masculinities and femininities, plays an important role in shaping when romantic relationships end. However, the relevance of gender culture is often underappreciated, in part because its empirical identification remains elusive. This study leverages cross-country variation in gender norms to test the hypothesis that gender culture conditions which heterosexual romantic relationships end and when. We analyze the extent to which male-breadwinning norms determine the association between men's unemployment and couple separation. Using harmonized household panel data for married and cohabiting heterosexual couples in 29 countries from 2004 to 2014, our results provide robust evidence that male-breadwinner norms are a key driver of the association between men's unemployment and the risk of separation. The magnitude of this mechanism is sizeable; an increase of one standard deviation in male-breadwinner norms increases the odds of separation associated with men's unemployment by 32 percent. Analyses also show that the importance of male-breadwinner norms is strongest among couples for whom the male-breadwinner identity is most salient, namely married couples. By directly measuring and leveraging variation in the key explanatory of interest, gender culture, our study offers novel and robust evidence reinforcing the importance of gender norms to understand when romantic relationships end.